2009
DOI: 10.1021/la902224t
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Thin Films Self-Assembled with a Partly Fluorinated Surfactant Template

Abstract: New TiO(2) films have been self-assembled on solid substrate by dip-coating using TiCl(4) as the titanium source and the partly fluorinated surfactant F(CF(2))(8)C(2)H(4)(OC(2)H(4))(9)OH as the liquid crystal template. By control over the dip-withdrawal speed, film thicknesses from a minimum of 43 nm were produced with rms roughnesses of 0.5-0.7 nm. The films were characterized by X-ray reflectivity, grazing incidence small-angle X-ray scattering, atomic force microscopy, contact angle measurements, and Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The physical thickness of the coating was obtained by fitting the Kiessig fringes in the XRR curve and measuring with a spectroscopic ellipsometer. 49,50 The results obtained by the two methods were marked as d XRR and d EP respectively as shown in Table 2. A good agreement between d XRR and d EP can be found, showing that the physical thickness is accurate.…”
Section: Coating Thicknessmentioning
confidence: 99%
“…The physical thickness of the coating was obtained by fitting the Kiessig fringes in the XRR curve and measuring with a spectroscopic ellipsometer. 49,50 The results obtained by the two methods were marked as d XRR and d EP respectively as shown in Table 2. A good agreement between d XRR and d EP can be found, showing that the physical thickness is accurate.…”
Section: Coating Thicknessmentioning
confidence: 99%
“…However, compared to silica materials it is difficult to obtain TiO 2 with stable mesostructure and the main challenge is to preserve the pore ordering upon surfactant removal. Even if most reported studies dealing with ordered mesostructured titania are focused on films, [7][8][9][10][11] some attempts have been made to prepare bulk ordered titania. Ionic surfactants were used initially because their amphiphilic nature provides well-organized micelles around which the titania framework can be assembled by electrostatic interactions.…”
mentioning
confidence: 99%
“…20,21 Moreover, we have recently shown that liquid crystals of R F 8 (EO) 9 can be used as a template for the preparation of new TiO 2 films. 10 The films have been self-assembled on a solid substrate by dip-coating using TiCl 4 as the titanium source. Their GI-SAXS patterns are characteristic of a 2-D hexagonal structure, in which tubular rods of the fluorinated surfactant are packed hexagonally and aligned parallel to the substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In previous examples from our laboratory and others, organic molecules have been used to direct the growth of inorganic materials into functional geometries. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Even high energy ion radiation has been used to texture titania films. 36,37 A patterning technique described by Masuda et al 38 and later improved by Goh et al 39 was used to create a porous structure in titanium dioxide that makes progress towards the ideal geometry.…”
mentioning
confidence: 99%